2015
DOI: 10.1002/hbm.22776
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter mapping of structural network alterations in autism

Abstract: Autism spectrum disorders (ASD) are a group of neurodevelopmental conditions primarily characterized by abnormalities in social cognition. Abundant previous functional MRI studies have shown atypical activity in networks encompassing medial prefrontal cortex (mPFC) and medial parietal regions corresponding to posterior cingulate cortex and precuneus (PCC/PCU). Conversely, studies assessing structural brain anomalies in ASD have been rather inconsistent. The current work evaluated whether structural changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 70 publications
11
90
0
Order By: Relevance
“…c Functional connectivity alterations showing primarily decreased connectivity between medial frontal and posterior midline regions in ASD relative to controls. Adapted from Valk et al (2015) and Di Martino et al (2014) with permission frontal cortex in 3/6 of cases (Bailey et al 1998). Another study observed laminar rearrangement together with a poorly defined gray and white matter interface in some specimens (Avino and Hutsler 2010).…”
Section: Probing Regional Morphologymentioning
confidence: 93%
See 2 more Smart Citations
“…c Functional connectivity alterations showing primarily decreased connectivity between medial frontal and posterior midline regions in ASD relative to controls. Adapted from Valk et al (2015) and Di Martino et al (2014) with permission frontal cortex in 3/6 of cases (Bailey et al 1998). Another study observed laminar rearrangement together with a poorly defined gray and white matter interface in some specimens (Avino and Hutsler 2010).…”
Section: Probing Regional Morphologymentioning
confidence: 93%
“…2a). While the authors reported a generally consistent direction of effects across each of the analysis sites, they emphasized variability in effects sizes across the sites (that may be due to variability in scanning parameters and inclusion criteria), together with increased effects in children compared to adults (Valk et al 2015).…”
Section: Probing Regional Morphologymentioning
confidence: 97%
See 1 more Smart Citation
“…Structural images were reconstructed using FreeSurfer, an automated segmentation tool that has been demonstrated to label structures comparably to manual tracing techniques (20). Although visual inspection is commonly used to qualitatively examine the quality of structural MRI data, more recent techniques have additionally allowed for quantitative measurements of anatomical data quality (38,39). To assess data quality in an unbiased manner, Freesurfer's QA tools (https://surfer.nmr.mgh.harvard.edu/fswiki/ QATools) were used to calculate signal-to-noise ratios for each subject as well as to generate a series of screenshots taken from various steps throughout the reconstruction pipeline.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, given this link to connectivity, structural covariance networks are particularly appealing to examine neuropsychiatric disorders in which aberrations in structural and functional networks have been implicated. Alterations in net-20 works of structural covariance have been demonstrated in autism (Zielinski et al, 2012;Bernhardt et al, 2014;Valk et al, 2015;Bethlehem et al, 2017), schizophrenia (Shi et al, 2012;Wheeler et al, 2014;Alexander-Bloch et al, 2014), epilepsy (Bernhardt et al, 2011;Yasuda et al, 2015;Bernhardt et al, 2016), and grapheme-color synesthesia (Hänggi et al, 2011), to name a few such disorders.…”
Section: Introductionmentioning
confidence: 99%